A methods engineering study on the University of the Philippines Press - Calayag, Laura N. (College of Engineering, 1998)
This project study applies techniques involved in Methods Engineering which deals with method study, work measurement, systems and procedures and job evaluation. The study is conducted in UP Press plant, a government owned establishment located inside the UP Diliman campus. It aims to increase the plant efficiency by improving cycle time and labor and machine efficiency. Completion of the study involved visiting and observing the working environment. Familiarization of plant's production was done through several tours within the plant and observing workers perform their jobs. From this documentation, areas of concern for each section that needs attention were looked into. The plant layout was found to be poorly arranged and ventilated thus making the working environment look messy and congested. Some equipment were found to be unfit for workers' convenience. Based on this, several adjustments and recommendations were provided. Inefficient methods were also observed in some sections. And with these observations, improved methods were analyzed and evaluated. In line with this study, alternatives were provided and rated. These recommendations are given to answer some of the plant's areas of concern giving the plant's management options for future implementation.